The Need for Chess in School and Its Role in the Dynamics of Child Development (Revue internationale du CRIRES : innover dans la tradition de Vygotsky, 2017)
The article describes the methodology for studying the dynamics of increasing the level of development of intellectual processes in children learning to play chess with the help of the reﬂective-activity approach. It describes the formation of the mental plan of ac-tion and position of agency (subjectness position) in the planning of the student’s own developmental trajectory and learning. The results of the inﬂuence of chess lessons on the qualitative leap in the development of junior students in comparison with children not engaged in chess are considered. The developing potential of chess lessons for students is also described.
Keywords: Intellectual processes; Cognitive processes; memory (visual-mediated and auditory); Attention; Working capacity; Ability to think logically on the verbal and nonverbal level; Ability to plan and predict the results of actions; Psychological research; Chess for the overall development; Mental plan of action; Position of agency (subjectness position); Zone of proximal development; Reflective-activity approach